Pengelolaan Zakat Profesi dalam Tinjauan Hukum Islam dan Peraturan Walikota No.18 Tahun 2018 di Baznas Kota Cimahi - Amila Vindi Oktaviana; Ramdan Fawzi; Popon Srisusilawati (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. The purpose of this study is to examine in more depth the management of professional zakat and also in the review of Islamic law and also look at the PERWALI Cimahi. The research method used is a normative qualitative method whose type of research is field research whose activities include interviews. By using primary data sources obtained from interviews, and secondary data referring to books, journals that will complement the results of existing interviews. Baznas Kota Cimahi already manages professional zakat in accordance with Islamic Law as stated by a 2003 fatwa collecting from salaries, and is also collected in accordance with opinions with a nishab of 2.5%. There are also several health, educational, humanitarian, economic, da'wah and advocacy programs for the distribution and utilization of zakat to people who are entitled to receive zakat 8 mustahik in accordance with the Qur'an Surat At-Tawbah verse 6. Baznas Kota Cimahi already manages professional zakat. Baznas Kota Cimahi has managed professional zakat in accordance with the Mayor of Cimahi City Number 18 of 2018, namely collecting according to Article 6 ASN who has income that has reached nishab must issue professional zakat, the income of civil servants for 1 (one) year that reaches nishab. Then collect the amount / nishab In accordance with Article 9, the amount of professional zakat collected is 2.5% (two point five percent) of the income received by ASN every month. Then report the results of collecting professional zakat, infaq, and shodaqoh from ASN Cimahi City local government to the Mayor through the Regional Secretary. Abstrak. Tujuan penelitian ini untuk meneliti secara lebih mendalam mengenai pengelolaan zakat profesi dan juga dalam tinjauan hukum Islam dan juga melihat dalam PERWALI Kota Cimahi. Metode penelitian yang digunakan adalah metode kualitatif normatif yang jenis penelitiannya adalah penelitian lapangan yang kegiatannya meliputi wawancara. Dengan menggunakan sumber data primer yang diperoleh dari wawancara, dan data sekunder mengacu pada buku, jurnal yang akan melengkapi hasil wawancara yang ada. Baznas Kota Cimahi sudah mengelola zakat profesi sesuai syariat Hukum Islam seperti yang disebutkan oleh fatwa tahun 2003 menghimpun dari gaji, dan juga dipungut sesuai dengan pendapat dengan nishab 2,5 %, juga diadakannya beberapa program kesehatan, pendidikan, kemanusiaan,ekonomi,dakwah dan advokasi untuk pendistribusian dan pendayagunaan zakat kepada orang yang berhak menerima zakat 8 mustahik sesuai dalam Al-Qur’an Surat At-Taubah ayat 6. Baznas Kota Cimahi sudah mengelola zakat profesi. Baznas Kota Cimahi sudah mengelola zakat profesi sesuai dengan PERWALI Kota Cimahi Nomor 18 Tahun 2018 yaitu menghimpun sesuai Pasal 6 ASN yang mempunyai penghasilan yang sudah mencapai nishab harus mengeluarkan zakat profesi, penghasilan ASN selama 1 (satu) tahun yang mencapai nishab. Lalu memungut dengan besaran/ nishab Sesuai Pasal 9 besaran zakat profesi yang dipungut sebesar 2,5 % (dua koma lima persen) dari penghasilan yang diterima ASN setiap bulan. Lalu melaporkan hasil pemungutan zakat profesi, infaq, dan shodaqoh dari ASN Pemerintah daerah Kota Cimahi kepada Wali Kota melalui Sekretaris Daerah.